Floristic Components of the Ground Flora of a Tropical Lowland Rain Forest at Gunung Mulu National Park, Sarawak - Kiew, Ruth (1978)
The floristic components of the ground layer at the Gunung Mulu National Park, Sarawak, are described. These components are associated with microhabitats. The microhabitats of the riverine system include the shallow stream, rocky banks and banks of larger rivers, and those of the shaded forest include permanently wet areas, rocky litter-free slopes, steep litter covered slopes, surfaces of logs, roots or rocks and the flat well-drained alluvial forest. Possible causes of the uneven distribution of the ground layer species of the flat well-drained alluvial forest are discussed. The species composition of this alluvial forest is compared with other published reports from the Danum Valley, Sabah and Pasoh Forest Reserve Malaya, and with some other lowland forest types such as kerangas and peat swamp forest in Sarawak. The phenomenon of iridescence and variegation of leaves is briefly noted.